Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1080/09553000110097208
|View full text |Cite
|
Sign up to set email alerts
|

Implication of PBP74/mortalin/GRP75 in the radio-adaptive response

Abstract: The results support the view that while PBP74 is necessary to the adaptive response, it may not by itself be sufficient for the adaptive response to occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
(2 reference statements)
1
30
0
Order By: Relevance
“…We note that as for the H cybrid, the heat induction of HSP60 gene is in line with literature data, while the up-regulation of the HSP75 gene is unexpected, as it had been reported to be up-regulated by stresses different from heat (Hadari et al 1997;Ryan et al 1997;Carette et al 2002;Zhao et al 2002;Tokalov et al 2003;Murray et al 2004;Voloboueva et al 2008). Considering the role of the two HSPs in the processes of protein import into mitochondria and subsequent protein folding (Frydman 2001;Mokranjac and Neupert 2005;Saibil 2008), we could hypothesize that mtDNA variability modulates mRNA levels of HSP60 and HSP75 through transcription factors that coordinate the activity of the two genes.…”
Section: Discussionsupporting
confidence: 75%
“…We note that as for the H cybrid, the heat induction of HSP60 gene is in line with literature data, while the up-regulation of the HSP75 gene is unexpected, as it had been reported to be up-regulated by stresses different from heat (Hadari et al 1997;Ryan et al 1997;Carette et al 2002;Zhao et al 2002;Tokalov et al 2003;Murray et al 2004;Voloboueva et al 2008). Considering the role of the two HSPs in the processes of protein import into mitochondria and subsequent protein folding (Frydman 2001;Mokranjac and Neupert 2005;Saibil 2008), we could hypothesize that mtDNA variability modulates mRNA levels of HSP60 and HSP75 through transcription factors that coordinate the activity of the two genes.…”
Section: Discussionsupporting
confidence: 75%
“…Unlike some members of the HSP70 family, Hsp75 is not heat-inducible, but is upregulated by glucose deprivation (GD), oxidative injury, and ultraviolet A irradiation (Carette et al, 2002;Hadari et al, 1997;Lee, 2001). Studies have indicated that Hsp75 upregulation suppresses apoptosis induced by arsenite in lung epithelial cells (Lau et al, 2004), mercury in renal cells (Stacchiotti et al, 2006), and glucose starvation and ischemia reperfusion in lung cells (Gao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Grp75 has been implicated in various biological processes of human cells (13) and has been shown to respond to numerous forms of stress, including ischemia (15), glucose deprivation (16), oxidative injury (22) and drug resistance (23). In addition, data from previous studies have shown that the treatment of IR led to the upregulation of the Grp75 protein (17,18). In this study, the expression of Grp75 induced by IR was highlighted and a dose/time-dependent induction of Grp75 expression in response to IR treatment was identified ( Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have reported that the expression of Grp75 is inducible in response to IR treatment (17,18). However, there is no evidence concerning whether the induction of the Grp75 gene depends on the amount of IR or the frequency of IR.…”
Section: The Expression Of Grp75 Was Induced By Ir In Pc12 Cellsmentioning
confidence: 64%
See 1 more Smart Citation